Assessing the Antenna Performance (Radiated Power) and Electromagnetic Impact (SAR) on a User of a Wearable RF Communication Device, Involving Variously Structured Models - Patryk Zradzinski; Jolanta Karpowicz; Krzysztof Gryz (IEEE Access)
The investigations focused on the significance of the structural design of models of a wearable device equipped with a wireless radiofrequency communication module (W-RFCD) operating at 2.45 GHz. Computer modeling was used to determine antenna performance (radiated power and related battery operating time), as well as the associated electromagnetic impact (SAR) in the user’s head. The findings showed a potential reduction in battery life of 20-40% for body-worn devices when used near the head, compared to their performance in free space, while maintaining the same quality of wireless connection. In the exposure scenarios examined, results revealed that the 10g-SAR in the user’s head could increase significantly: 1) by up to 65% when the RF module’s battery was centered, versus when it was offset; and 2) by up to 240% with a 0 mm distance between the RF module and the battery, compared to a 2 mm distance. The use of a simplified model of W-RFCD may lead to incorrect conclusions about its performance and a substantial underestimation of the SAR values (10g-SAR values are up to double in the most complex exposure scenarios examined, compared to the most simplified). The antenna performance and SAR of W-RFCD developed using ready-made components can be optimized without altering antenna matching circuits or inserting additional physical structures.